Machine Learning and Data Mining in Pattern Recognition 10th International Conference, MLDM 2014, St. Petersburg, Russia, July 21-24, 2014, Proceedings - Perner, Petra (Lecture Notes in Artificial Intelligence, 2014)
This book constitutes the refereed proceedings of the 10th International Conference on Machine Learning and Data Mining in Pattern Recognition, MLDM 2014, held in St. Petersburg, Russia in July 2014. The 40 full papers presented were carefully reviewed and selected from 128 submissions. The topics range from theoretical topics for classification, clustering, association rule and pattern mining to specific data mining methods for the different multimedia data types such as image mining, text mining, video mining and Web mining.